Kepastian Hukum Kepemilikan Hak Atas Tanah Dalam Terjadi Overlap Tanah - Akhila Rayintama, I Gde; Udiana, I Made (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
This study was carried out with the aim of understanding the position of SHM on land with certificates issued from PTSL and aims to understand the application of Supreme Court Decision Number 1318/K/Pdt/2017 when land overlap occurs. This research applies normative legal research methods with a focus on studying related legal rules, legal principles, legal concepts, court decisions and legal doctrine using interpretation, description, argumentation and evaluation analysis techniques. The findings from this study are that the SHM for land that was issued previously and the certificate issued from PTSL both have authentic evidentiary power, but what is different is that if the certificate issued has defects, either material defects or formal defects, this will affect the legality of its position. as evidence of ownership or control of land that is not authentic. The results of further research show that the Supreme Court Decision Number 1318/K/Pdt/2017, which has become jurisprudential, can override government regulations in the event of overlapping land on multiple certificates in one land object. Thus, the Supreme Court's decision to this day remains a reference for Judex Pactie in deciding similar cases so that legal certainty and guarantees can be realized.